Description of the larvae of three species of Laccophilus Leach and comments on the phylogenetic relationships of the Laccophilinae (Coleoptera: Dytiscidae) - Michat, Mariano C. (Zootaxa, 2008)
The larvae of three Neotropical species of the diving beetle genus Laccophilus Leach (Laccophilus obliquatus Régimbart, L. paraguensis Régimbart and L. testudo Régimbart) are described and illustrated for the first time, with an emphasis on morphometry and chaetotaxy of the cephalic capsule, head appendages, legs, last abdominal segment and urogomphi. Larvae of these species lack the primary setae LA10 and LA12, and have the primary seta CO7 articulated proximally on all coxae, two apomorphies that define the subfamily Laccophilinae. They are also characterized by a frontoclypeus truncate proximally in the first instar, the presence of pectens on legs, and the presence of secondary setae on first urogomphomere. These character states are apomorphies that define the genus Laccophilus Leach. The absence of pore PAc and the presence of a dense group of secondary spiniform setae dorsally at the base of the siphon in instar III may also characterize this genus, as similar states are not found in other dytiscids. On the other hand, L. obliquatus, L. paraguensis and L. testudo differ from the other species of Laccophilus known in detail in the presence of an additional seta on the stipes and in the absence of pore ABc. Brief comments on the putative phylogenetic relationships of Laccophilinae and Laccophilus inferred from larval morphology, as well as on the characters potentially useful in studying relationships within the group are presented.